Analisis Pelaku Hukum Ekonomi dalam Pengelolaan Organisasi Bisnis - Nuha Nur Afifah; Misnawati (Medan Resource Center, 2026)
Business organizations operate within an increasingly complex legal environment that requires effective governance and strict regulatory compliance. This study investigates the roles, responsibilities, and compliance of economic law actors in the management of business organizations by addressing how these actors contribute to lawful, accountable, and sustainable business practices. The research employs a qualitative approach based on a comprehensive literature review of legal regulations, scholarly publications, and relevant doctrinal sources. The findings reveal that economic law actors perform strategic functions in policy formulation, organizational supervision, risk management, and ensuring that business activities comply with applicable legal frameworks. The study also demonstrates that their legal, professional, and social responsibilities must be exercised in good faith, with integrity, transparency, and accountability to minimize legal disputes and strengthen corporate governance. The study concludes that optimizing the performance and legal awareness of economic law actors is fundamental to promoting legal certainty, protecting stakeholders' interests, and establishing a fair, orderly, and sustainable business environment.